2018
DOI: 10.2147/orr.s157864
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial impingement syndrome: management challenges

Abstract: The painful shoulder is the most common condition seen in specialist shoulder clinics. It is often associated with lack of range of motion and reduced shoulder function. Lack of sleep and difficulties in performing basic daily life activities are common findings. Subacromial Impingement Syndrome (SAIS) has been considered as the most common cause of shoulder pain since it was described in 1852. Charles Neer, in 1972, described the presence of a “proliferative spur and ridge” on the undersurface of the acromion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 50 publications
1
37
0
15
Order By: Relevance
“… 34 Future randomized controlled trials should examine the combined effects of CARE and exercise, as most studies have shown no difference in outcome between impingement syndrome patients randomized to surgical decompression or conservative management. 35 Thus, it is always desirable to start with conservative rehabilitation treatment, administering surgical treatment only in select cases. The optimal treatment for shoulder impingement syndrome remains unknown, 26 and exercise is still the most important treatment component for this disorder.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Future randomized controlled trials should examine the combined effects of CARE and exercise, as most studies have shown no difference in outcome between impingement syndrome patients randomized to surgical decompression or conservative management. 35 Thus, it is always desirable to start with conservative rehabilitation treatment, administering surgical treatment only in select cases. The optimal treatment for shoulder impingement syndrome remains unknown, 26 and exercise is still the most important treatment component for this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Impingement syndrome is currently estimated to represent 44-65% of all shoulder pain disorders [1]. The most normal causes of symptoms are extrinsic causes such as work and sport overload [2].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting element emerges from the results of questions regarding the choices of therapeutic strategies for the patient. There is strong evidence suggesting that physiotherapy treatment is the best conservative strategy initially and for short-term effects [ 4 , 12 , 65 ]. OMPTs from the current study were more aware than orthopaedic surgeons about this, with a statistically significant difference in all three questions dedicated to this topic.…”
Section: Discussionmentioning
confidence: 99%